A semiotic analysis of the novel "Cantik itu Luka" by Eka Kurniawan - Nahdoh, Wardhatun; Syamsurrijal; Hadi , Muhammad Zaki Pahrul (Jurnal Ilmu Sosial dan Humaniora, 2024)
Literary work is the arrangement of concepts that are imagined into writing that has aesthetic and moral values. In addition, literary works must be able to produce beautiful works of art. Many elements are involved in the creative process of literary works, including science, insights, thoughts, beliefs, and real experiences, as well as elements of the author's imagination. Besides having structural elements, novels also have semiotic elements, which study the structures, rules, and conventions that make signs have meaning and significance. This research aims to identify the semiotic elements in Eka Kurniawan's novel "Cantik Itu Luka". In this study, researchers used semiotic theory according to the views of Charles Pierce. After researching, the novel "Cantik itu Luka" by Eka Kurniawan shows a lot of semiotic word usage , such as icon (topeng wayang, pabrik, kucing hitam), index ( jejak kaki di hutan, hujan ders, merokok), and symbol ( bunga, api, rokok). Researchers use a qualitative descriptive method, or a descriptive method accompanied by analysis activities, to obtain data. The data was obtained by reading Eka Kurniawan's book "Beautiful Is Hurt" and analyzing it semiotically, finding many explicit signs. Utilizing this analysis, readers should be educated to appreciate literary works and understand the semiotic system in them.